2021
DOI: 10.1007/s11524-021-00578-3
|View full text |Cite
|
Sign up to set email alerts
|

Congestion Pricing Policies and Safety Implications: a Scoping Review

Abstract: Congestion pricing policies (CPPs) are a common strategy for addressing urban traffic congestion. Research has explored several impacts of these policies (e.g., air quality, equity, congestion relief). The purpose of this review was to synthesize findings from publications examining CPP impacts on road user safety outcomes. We conducted a systematic search of relevant literature in four large research databases (Transport Research International Documentation, Web of Science, PubMed, and Scopus), searching from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to (Shatanawi et al, 2020), in the congestion charge policy, the congestion charge scheme for each area or city must be designed uniquely for the best results. In addition, the potential benefits of implementing congestion pricing policies may vary according to the length of time after implementation and the type of road user (Singichetti et al, 2021).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…According to (Shatanawi et al, 2020), in the congestion charge policy, the congestion charge scheme for each area or city must be designed uniquely for the best results. In addition, the potential benefits of implementing congestion pricing policies may vary according to the length of time after implementation and the type of road user (Singichetti et al, 2021).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Previous research has indicated the potential of travel demand management strategies, e.g., congestion pricing, promoting public transport, and teleworking, in reducing traffic crashes (Litman, 2012;Litman, 2015;Singichetti et al, 2021). Several studies have developed macroscopic crash prediction models to demonstrate the positive impacts of increasing public transport usage (Moeinaddini et al, 2015; and teleworking (Pirdavani et al, 2014) on traffic safety.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this research (Singichetti et al, 2021), we propose a new method for modeling internet bandwidth requirements on campus, namely by combining engineering and statistical methods. The research case study was conducted at the Sultan Syarif Kasim State Islamic University (UIN Suska) Riau, by mapping the contribution of each content accessed by the campus academic community.…”
Section: Introductionmentioning
confidence: 99%